2021
DOI: 10.24251/hicss.2021.044
|View full text |Cite
|
Sign up to set email alerts
|

Digital Facilitation Assistance for Collaborative, Creative Design Processes

Abstract: People focus more and more on creating innovations collaboratively. Digital assistants (DAs) can accelerate such collaborative, creative design processes by supporting people in their work. Especially in the context of design, such as design thinking, moderators that facilitate collaborative, creative workshops can benefit from the support for their teams and themselves in the form of a DA. Based on interviews with experienced workshop facilitators from research and practice, we discuss implications for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…Digital experience enhancement refers to decisions about customer needs based on customer information collected and integrated using algorithms [18]. The internal enabler, or digital facilitation, uses digital platforms and technologies to promote employee collaboration [55]. One of the internal challenges that employees may have in improving the digital customer experience is decision-making centralization [56]; therefore, decentralization promotes the transfer of power and decision-making from a central entity to a distributed network [57].…”
Section: Building Digital Transformation Dynamic Capabilities To Gene...mentioning
confidence: 99%
“…Digital experience enhancement refers to decisions about customer needs based on customer information collected and integrated using algorithms [18]. The internal enabler, or digital facilitation, uses digital platforms and technologies to promote employee collaboration [55]. One of the internal challenges that employees may have in improving the digital customer experience is decision-making centralization [56]; therefore, decentralization promotes the transfer of power and decision-making from a central entity to a distributed network [57].…”
Section: Building Digital Transformation Dynamic Capabilities To Gene...mentioning
confidence: 99%
“…While the first three phases of the DT process -such as delivering information and suggestions [3], as well as analyzing data [25] can be implemented well through AI, applications that address ideation and other creative processes are lacking [28]. A large number of research articles already address the collaboration between humans and technologies such as AI, showing a great potential of AI for the future of work [29][30][31][32]. Specific factors such as trust and skepticism towards AI [33][34] are already being explored.…”
Section: Artificial Intelligence and Conversational Agentsmentioning
confidence: 99%
“…Skills and experience of the person facilitating are decisive for the success of a creative collaboration. To relieve the facilitators, or to meet the high demand of these, (partial) tasks can be performed by Conversational Agents (CAs) -intelligent software that can understand and use natural language in written or spoken form (Bittner et al, 2021). Several studies have already demonstrated the successful use of CAs in supporting creativity (Tavanapour et al, 2019;Tavanapour and Bittner, 2018;Bittner et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Through developments in Machine Learning (ML) and artificial Intelligence (AI), CAs are becoming increasingly capable in processing and responding to user input (Seeber et al, 2018). However, many characteristics have not yet been explored (Bittner et al, 2021;Seeber et al, 2018). In particular, there is a need for CAs to appear more human, e.g., by responding empathically (Debowski et al, 2021), or knowing how to deal with creative context (Tavanapour et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation